THE EFFORTS OF ISA BOLETINI BEFORE THE OPENING OF THE RUSSIAN CONSULATE IN KOSOVSKA MITROVICA (Heritage, 2020)
The role of Isa Boletini in the time of the opening of the Russian consulate in Kosovska Mitrovica was of crucial political importance for the Serbian people living there. It was the time of intense Albaniansoppression, which went unnoticed or ignored by the Turkish authorities. In the beginning, Isa Boletini was the protector of the Serbian population, whose consuls in Priština reported no crimes committed by him. Meanwhile, his actions reversed course. His activities were aimed against the Serbian people and the Turkish authorities, who in turn started losing their standing with the Albanians. With the growing support from the Austro–Hungarian Empire, the Albanians leaders organized numerous gatherings, which adversely affected the Serbian population. Those gatherings resulted in gradual renunciation of obedience such as avoiding to pay the Ottoman tax to the Sultan. Albanians opposition to the Russian consulate in Mitrovica rose to prominence. Consequently, the Russian representatives urge Constantinople to request for the Isa Boletini be removed from Mitrovica. The Sultan yielded to the Russian request, while Isa Boletini resisted and tried to bargain for himself, but eventually left for Constantinople. He hoped that the support of the local Albanians leaders would assure his swift return. His absence did not improve the position of the Serbian people, who were continually exposed to extortion and taxes.
Keywords: Isa Boletini, Serbs, Albanians, Mitrovica, Ottoman Empire, Russian Consulate.